AKTIVITAS ANTIMIKROBA BAKTERI ENDOFIT (Pseudomonas Berfluoresen) DARI AKAR PISANG BUAI (Musa x paradisiaca L.) - Astrid; Dwi Hilda Putri; Dezi Handayani (Universitas Cokroaminoto Palopo, 2026)
Infectious diseases caused by pathogenic bacteria and fungi remain a global health problem, particularly due to the increasing incidence of antimicrobial resistance, highlighting the need for effective alternative antimicrobial sources. Endophytic bacteria, especially fluorescent Pseudomonas, are known to produce secondary metabolites with antibacterial and antifungal properties. This study aimed to evaluate the antimicrobial activity of endophytic fluorescent Pseudomonas isolated from the roots of banana buai (Musa × paradisiaca L.) and to identify isolates with the highest activity. This experimental study employed a Completely Randomized Design (CRD) using 44 isolates with three replications. Antimicrobial activity was tested in vitro using the spot inoculation method against Escherichia coli, Staphylococcus aureus, and Candida albicans. The observed parameter was the diameter of the inhibition zone, which was analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test. The results showed that antimicrobial activity varied among isolates and was specific to the test microorganisms. Isolate PFPB 32 exhibited the highest activity against E. coli and S. aureus, while isolate PFPB 300 showed the strongest antifungal activity against C. albicans. These findings indicate that endophytic fluorescent Pseudomonas from banana buai roots have potential as a source of antimicrobial agents, particularly antifungal agents against Candida albicans